Human Resource Management Factors That Influence To Employees Performance - Mohammad Amir Furqon Hayat (Yos Soedarso Economic Journal (YEJ), 2019)
Purpose of this research is to know the most dominant factor influencing (that influences) to employees performance in PT. Telkom Sampang.Object of this research uses population sample to all employees in PT. Telkom Sampang, and the total  respondents are 45 employees.In this research, there are two kinds of analysis. They are qualitative and quantitative analysis. Qualitative analysis is to get description about object condition examined. This analysis will describe respondents’ answer by using likert scale. Beside that quantitative analysis is to get description about object condition examined by multiple linear regression.Based on research discovery and discussion abaut knowledge point of human resource manajement factors that are consist of recruitment, development and prosperity, it can be concluded as follow.On presentation analysis, partially or by t-test, Human resource management that is dominant influencing to employees performance done by PT. Telkom Sampang is prosperity factor.Based on research result, it’s concluded that hypothesis is independent variable. It’s human resource management consisted of same factors. They are recruitment, development and prosperity factors. The factors influence to employees performance in PT. Telkom Sampang has been proven right. Suggestion that can be given on this research to employees performance, human resource management done by PT. Telkom Sampang should be more enhanced. So that employees as social attendant in telecomunication sector think getting more attention. Keywords : Recruitme; Development; Prosperity; Employees Performance